Níveis de BDNF no córtex pré-frontal de ratos submetidos à estimulação epidural por corrente contínua (EECC) de baixa intensidade - Custodio, Juliana Cardoso de Souza (2017)
The nervous system (NS) has the ability to modify its morphofunctional organization in response to internal changes or external demands, This adaptive capacity constitutes brain plasticity. Brain-derived neurotrophic factor known as BDNF has attracted considerable attention in the scientific literature for its involvement in crucial processes of nervous system development and regulation, however, many aspects of this molecule are still unknown. It is known that different protocols using brain stimulation have already shown positive effects on cognition and cortical function improvement, and BDNF may be potentially involved in this process. Objective: To investigate the changes in BDNF levels in the medial prefrontal cortex (CPFm) of adult rats undergoing acute and chronic cortical modulation with different polarities, through lowintensity DC epidural stimulation.